2017
DOI: 10.1038/s41598-017-01858-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 CRF01_AE strain is associated with faster HIV/AIDS progression in Jiangsu Province, China

Abstract: The goal of this study was to assess risk factors associated with HIV/AIDS progression. Between May 2007 and December 2014, 114 subjects were enrolled in Wuxi City and examined every 6 months. The pol gene sequence was amplified to ascertain the HIV-1 subtype. A Cox proportional hazards regression model was used to estimate the factors associated with HIV/AIDS progression. The median follow-up time for all 114 subjects was 26.70 months (IQR: 18.50-41.47), while the median progression time of the 38 progressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 35 publications
3
38
1
1
Order By: Relevance
“…CRF01_AE has been shown to be associated with a lower CD4 + T cell count and higher rates of CXCR4 coreceptor [7,8,36]. In our study, baseline CD4 + T cell count was lower in the CRF01_AE group than the non-CRF01_AE group.…”
Section: Discussionsupporting
confidence: 42%
“…CRF01_AE has been shown to be associated with a lower CD4 + T cell count and higher rates of CXCR4 coreceptor [7,8,36]. In our study, baseline CD4 + T cell count was lower in the CRF01_AE group than the non-CRF01_AE group.…”
Section: Discussionsupporting
confidence: 42%
“…CRF01_AE has been shown to be associated with a lower CD4 + T cell count and higher rates of CXCR4 co-receptor [7,8,36]. In our study, baseline CD4 + T cell count was lower in the CRF01_AE group than the non-CRF01_AE group.…”
Section: Discussionsupporting
confidence: 43%
“…Our study further demonstrates that CRF01_AE patients have a lower CD4+ cell count than those with CRF07_BC, CRF08_BC, or other genotypes at initial diagnosis in a large population with different transmission routes. Previous studies have suggested that CRF01_AE is associated with faster AIDS progression (defined as CD4+ T-cell counts decreasing to < 200 cells/ μl or < 350 cells/μl) compared to that with non-CRF01_AE 10,11 . We demonstrate for the first time that patients with CRF01_AE exhibit a significantly higher mortality compared than those with CRF07_BC, CRF08_BC, and other genotypes, in a large observational cohort study.…”
Section: Discussionmentioning
confidence: 98%